PELATIHAN INSTALASI LISTRIK UNTUK MENINGKATKAN KETERAMPILAN DALAM UPAYA PENINGKATAN PENDAPATAN WIRAUSAHA BAGI PEMUDA PUTUS SEKOLAH DI DESA KRUENG SEUNONG - Wahyuni, Sri; Febriansyah, Sutan; Nasruddin, Nasruddin; Eviyanti, Cut Yuniza; Rista, Lia (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2022)
The failure of formal education is not the end of everything. Young people who have failed in the formal education can still hone their skills and knowledge in non formal education through trainings to increase their capacity. STIE and STKIP Bumi Persada Lhokseumawe lecturers are designed and conducted electrical installation training to improve their abilities and skills in Krueng Seunong Village. The purpose of this activity is to enable young out of school to be able to independently install and repair electrical installations, thereby opening up entrepreneurshipl opportunities and at least having an income for themselves. This activity is carried out in three approaches, that is: briefing material, training and demonstration, and testing. The results obtained are the participants success in using and flowing electric current to the media which is marked by light up in each installed circuit.